The geology of post-Chuniespoort deposits in the Verwoerdburg area south of Pretoria with specific reference to engineering properties of the red soils - Eriksson, Patrick George (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1985.